Competition, Monopoly and Countervailing Power - Adams, Walter (Quarterly Journal of Economics, 1953)
I. Introduction, 469. — II. Top-level financial control and vertical integration, 472. — III. Bilateral monopoly and countervailing power, 475. — IV. Technological and inter-industry competition, 477. — V. The role of government, 480. — VI. Size, technology, and efficiency, 487. — VII. Conclusion, 491.